Voltage Stability Enhancement in Power System using STATCOM based on Specific Coefficient Algorithm (SCA) - Vijayan, Asha; Karthikeyan, R. (Asian Journal of Electrical Sciences, 2014)
The countries like India with increasing demand of electric power day by day it is difficult to expand the existing transmission system due to difficulties in right of way and cost problem in transmission network expansion. So, we need power flow controllers to increasing transmission capacity and controlling power flows Increased demands on transmission, absence of long-term planning, and the need to provide open access to generating companies and customers, all together have created tendencies toward less security and reduced quality of supply. Due to increase in demand, the transmission system becomes more stressed, which in turn, makes the system more vulnerable to voltage instability. Voltage stability plays an important role in the operation of the power system and there are major concerns about it for better utilizations of the system. Improvement in power system performance can be obtained using flexible AC transmission systems (FACTS). FACTS devices are capable of the simultaneous control of the bus voltage and real and reactive power flow in transmission systems independently; but because of excessive cost, the number and the location of these devices should be indicated optimally. This paper proposes a method of optimization of STATCOM allocation based on specific coefficients algorithm (SCA) to specify the number, location and input values by minimizing the voltage indices of system buses. The proposed SCA noticeably improves the accuracy and performance of traditionally used optimization processes especially in large scale networks. This method is applied to the 14-bus IEEE standard system. The results of ordinary and new optimization algorithm have shown the great improvement in optimization process using SCA.